The Role of the Civil Service Police in Handling Public Peace and Order in East Lombok Regency 2000-2020 - Bambang Eka Saputra; Abdul Hafiz; Abdul Rasyad; Lalu Murdi; Muhammad Shulhan Hadi; Muchamad Triyanto (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
The existence of the Civil Service Police (Pol-PP) in the historical trajectory of the Indonesian nation has become an inseparable part of the administration of government, both from the Dutch colonial period until Indonesia's independence. The role of Pol-PP in realizing peace and tranquility in East Lombok is part of the routine agenda of the local government. This study aims to determine the history of the establishment of Pol-PP in Indonesia and East Lombok. Knowing the role of Pol-PP in maintaining and overcoming public peace and order in East Lombok. The historical research method is used to reveal the existence and role of Pol-PP in maintaining security and order in the wheels of government in East Lombok. The stages of the historical method are carried out through heuristics, criticism, interpretation, and historiography. The results of the study indicate that the Pol-PP in East Lombok has made a significant contribution to the success of the East Lombok regional government in maintaining peace and order in the community in particular. This was realized from the period 2000-20020 where the role and function of Pol-PP went well.